THE FUTURE OF ART EDUCATION. - Gawthrop, Rob; Stooke, Andrew J. (Art Monthly, 2008)
Two letters to the editor are presented in response to articles in previous issues including the provision of art in higher education, and "Opting Out," by J. J. Charlesworth.